Variability Studies of Mustard Genotypes [Brassica juncea (L.) Czern and Coss] for Quantitative Traits and Yield Components at Satna District of Madhya Predesh (India) (International Journal of Food and Nutritional Sciences, 2022)
Twenty diverse cultivars of mustard in a Completely Randomized block design (CRBD) at AKS University, Satna, during Rabi season on November 2021. Data were collected for twelve quantitative traits and estimated for variance, genetic variability, heritability and genetic advance. The design of the experiment indicated highly significant differences for all the characters due to treatments. The analysis of variance indicated the existence of sufficient amount of variability among genotypes for all the studied characters. PCV was higher than GCV for all the studied characters. The maximum GCV and PCV was observed in no. of siliqua/plant followed by primary branches/plant, test weight (1000 seed) (g), seed yield/plant (g) and biological yield per plant (g). Higher estimates (h2b) >80% were observed for all the characters except number of seed/siliqua, harvest index (%) and seed yield/plant (g). High estimate of expected genetic advance at 5% were found for number of siliqua/plant followed by primary branches/plant, test weight (1000 seed)(g), biological yield/plant (g), and seed yield/plant (g). High heritability coupled with high genetic advance indicated the predominance of additive gene action in the expression of these traits.